Genetic variation in CFH predicts phenytoin-induced maculopapular exanthema in European-descent patients. (23rd January 2018) - McCormack, Mark; Gui, Hongsheng; Ingason, Andrés; Speed, Doug; Wright, Galen E.B.; Zhang, Eunice J.; Secolin, Rodrigo; Yasuda, Clarissa; Kwok, Maxwell; Wolking, Stefan; Becker, Felicitas; Rau, Sarah; et al.
Abstract : Objective: To characterize, among European and Han Chinese populations, the genetic predictors of maculopapular exanthema (MPE), a cutaneous adverse drug reaction common to antiepileptic drugs. Methods: We conducted a case-control genome-wide association study of autosomal genotypes, including Class I and II human leukocyte antigen (HLA) alleles, in 323 cases and 1, 321 drug-tolerant controls from epilepsy cohorts of northern European and Han Chinese descent. Results from each cohort were meta-analyzed. Results: We report an association between a rare variant in the complement factor H–related 4 ( CFHR4 ) gene and phenytoin-induced MPE in Europeans ( p = 4.5 × 10 –11 ; odds ratio [95% confidence interval] 7 [3.2–16]). This variant is in complete linkage disequilibrium with a missense variant (N1050Y) in the complement factor H ( CFH ) gene. In addition, our results reinforce the association between HLA-A*31:01 and carbamazepine hypersensitivity. We did not identify significant genetic associations with MPE among Han Chinese patients. Conclusions: The identification of genetic predictors of MPE in CFHR4 and CFH, members of the complement factor H–related protein family, suggest a new link between regulation of the complement system alternative pathway and phenytoin-induced hypersensitivity in European-ancestral patients.